Multimodality across communicative settings, discourse domains and genres - Bonsignori, Veronica; Camiciottoli, Belinda Crawford (Cambridge Scholars Publishing, 2016)
This volume focuses on multimodality in various communicative settings, with special attention to how non-verbal elements reinforce and add meaning to verbal expressions. The first part of the book explores issues related to the use of multimodal resources in educational interactions and English language classroom teaching, also involving learners with disabilities. The second part, on the other hand, investigates multimodality as a key component of communication that takes place in different specialized domains and genres. The book reflects a variety of methodological approaches that are grou.